PENERAPAN PENDEKATAN TEACHING AT THE RIGHT LEVEL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MATERI LUAS BANGUN DATAR - Dwi Puspita Martika; Diah Yovita Suryarini; Mawan Dwiyanto (Al-SAMBASY: Jurnal Kajian Pendidikan, 2025)
The low ability of students in understanding the concept of flat area is a problem that is often found in elementary schools. This study aims to analyze the effectiveness of Teaching at the Right Level (TARL) approach in improving the learning outcomes of fourth grade students on the material of flat area. The research method used is classroom action research (PTK) with a design that includes four stages: planning, implementation, observation, and reflection. The research subjects were fourth grade students with a total of 28 students. Data collection was done through learning outcome tests, student activity observations, and documentation. The results showed a significant increase in students' ability to understand the concept of flat area after the implementation of the TARL approach. In the pre-action stage, the average student score only reached 65.3 with 42.8% learning completeness. After the implementation of TARL, in cycle I the average score increased to 75.6 with 67.9% learning completeness, and in cycle II it reached 85.4 with 89.3% learning completeness. The TARL approach proved to be effective in identifying students' individual ability levels, providing appropriate scaffolding, and improving students' conceptual understanding and mathematics learning outcomes on flat area material.